Relatório de Estágio Profissional "Em busca de um sonho: ser professor de Educação Física" - Diogo Manuel Simões Figueiredo (2017)
This report relates the lived experiences of an intern teacher of Physical Education during your Professional Internship. This Internship was part of the second cycle of leading studies to master's degree in Teaching of Physical Education in the Middle School and High School from Sport College of University of Porto. This experience took place in a Group of Schools localized in the city of Barcelos. All of this process was supervised by an Advisor Teacher who exercise her functions in the Sport College of University of Porto and by a Cooperating Teacher of the host institution. All of the daily work and the cooperation between all of the internship core with the remaining school community was extremely important for the personal and professional growth. The document it is divided into eight chapters listed in this way: (1) Introduction; (2) Personal Dimension- where is developed my biographical course and the expectations about the Professional Internship; (3) Framework of Professional Practice - I introduce the Legal Institutional Framework, the internship core, the Helpful Schools Group and the assigned schools in the practice; (4) Achievement of the Professional Practice - is based on reflexive moments during all the process of teaching-learning of the intern year, giving an image of the most outstanding experiences. All of this moments results of the tasks embraced on the plane, achievement, evaluation, activities in which the internship core participated; (5) Investigation Study- I introduce a study about motivation; (6) Final paper- I put on evidence all the Professional Internship and I introduce my future expectations; (7) Bibliographic References (8) Attachments.